Revitalisasi Sastra Daerah Sebagai Upaya Pelestarian Identitas Budaya Nusantara - Davit (CV. SINAR HOWUHOWU, 2025)
Regional literature is a fundamental pillar of Nusantara's cultural identity, embodying local wisdom and collective memory. However, its existence is now under serious threat from globalization and language shift, leading to a disruption in intergenerational transmission. This article aims to analyze the urgency and strategies for revitalizing regional literature as an effort to preserve cultural identity. Using a qualitative method based on a library research approach, this study synthesizes various scholarly literature to construct a comprehensive conceptual framework. The findings indicate that a passive preservation approach is no longer adequate. An effective revitalization strategy must be holistic, resting on three main pillars: integration into formal education, innovation through digital platforms, and the empowerment of local communities as the primary agents. The revitalization of regional literature is not merely an act of heritage preservation but a strategic investment to enrich the nation's intellectual treasury and strengthen its identity, grounded in the spirit of Bhinneka Tunggal Ika (Unity in Diversity).